IMPLEMENTATION OF THE AGRICULTURAL INDEPENDENCE DEVELOPMENT PROGRAM FOR INMATES AT THE CLASS IIA CORRECTIONAL INSTITUTION IN KEDIRI - Indaka Prasetyo; Umar Anwar; Budi Priyatmono; Ali Muhammad (Universitas Nusa Cendana, 2026)
This study examines the implementation of the agricultural independence development program at the Class IIA Kediri Correctional Institution. The program has not been implemented optimally because there is no specific agricultural development framework within the institution, and only a small number of inmates participate despite the availability of relatively large agricultural land. The purpose of this study is to analyze how the agricultural development program is implemented, identify the obstacles faced, and evaluate its contribution to social reintegration and food security. The research uses a descriptive qualitative approach, with data collected through observation, interviews, and document analysis conducted at the Assimilation and Education Facility (SAE). The findings show that the program is carried out through a practical “learning by doing” approach, where inmates are directly involved in agricultural activities. This program provides benefits by equipping inmates with basic agricultural skills and contributing to the availability of food supplies for the correctional institution. However, its implementation still faces several challenges, including limited budget allocation, low inmate participation, lack of staff expertise in agriculture, and weather conditions that affect agricultural productivity. Although the program contributes to social reintegration and supports food security, its impact remains limited due to the small scale of implementation. Therefore, improvements are needed through increased inmate participation, better staff training, and the development of strategies that can adapt to climate conditions. The proposed “OPTIMIS” program offers a solution by strengthening collaboration with the Agriculture Department and universities, providing more structured training, and offering incentives such as certificates for participating inmates, so that the program can have a broader impact on social reintegration and institutional food security. Keywords: Program Implementation; Food Security; Kediri Class IIA Prison; Self Reliance Development; Agriculture; Social Reintegration